Pengaruh Media Google Sites Berbasis Kearifan Lokal Terhadap Literasi Budaya Siswa Kelas IV Sekolah Dasar - Hakim, Gus Nurman; Parmadi, Bambang; Yusnia (Universitas Bengkulu, 2026)
This study aims to analyze the effect of using Google Sites as a local knowledge-based learning medium on the science cultural literacy of grade IV students at SDN Cluster XVII, Bengkulu City. Utilizing a quasi-experimental methodology with a Matched Only Pretest-Posttest Control Group design, this research involved grade IV A (control) and IV B (experimental) students from SDN 11 Bengkulu City, selected via purposive sampling. Data collection instruments consisted of pre-tests and post-tests aligned with cultural literacy indicators. Statistical analysis revealed a significant difference between the two groups. Hypothesis testing yielded a tcount of 2.110 with a significance (2-tailed) of 0.039. Comparing this to the ttable at df 37 with a significance level of a = 0.05 (2.026), it is proven that tcount> ttable (2.110 > 2.026) and the significance value is less than 0.05. A comparison of average post-test scores shows the experimental group outperformed the control group, with scores of 71.00 and 58.42, respectively. This data confirms that implementing Google Sites as a learning medium integrating local knowledge has a significantly positive impact on improving students' cultural literacy. Consequently, the alternative hypothesis (Ha) is accepted. This study concludes that integrating digital technology via Google Sites is an effective science education strategy, enhancing both students' cognitive understanding and their cultural literacy. This media has proven capable of optimizing teaching and learning processes within SDN Cluster XVII, Bengkulu City, while serving as a valuable reference for teachers developing innovative, locally-based teaching materials that effectively engage students in their learning.